P5 Multiple micronutrient supplementation in pregnancy and long-term health outcomes in children: A systematic review and meta-analysis. (27th April 2016) - Devakumar, D; Fall, CHD; Sachdev, HS; Margetts, BM; Osmond, C; Wells, JCK; Costello, A; Osrin, D
Abstract : Background: Optimising maternal nutrition is important for improving child health in both the short and longer term. Micronutrient deficiency is common in women in low- and middle-income countries (LMICs). Multiple micronutrient supplementation in pregnant women reduces the proportion of babies born with low birth weight and has recently been recommended to improve child survival, growth and health. We reviewed the evidence that multiple micronutrient supplementation influences mortality and health outcomes in childhood. Method: We searched systematically for follow-up reports from all trials in a 2012 Cochrane review of multiple micronutrient supplementation in pregnancy. The intervention group included three or more micronutrients. The control group received iron and folic acid. Median time of onset varied from 9 to 23 weeks. Primary outcomes were offspring mortality, height and weight expressed as z scores, and head circumference, presented as unadjusted differences in means or proportions (intervention minus control). Secondary outcomes included other anthropometry, body composition, blood pressure, cognitive outcomes and lung function. Results: Nineteen follow-up reports were found from nine trials. Six of the trials used the UNIMMAP supplement containing 15 micronutrients in their recommended daily allowances. The other three trials had similar constituents and doses. Data for mortality estimates were available from all trials. Meta-analysis (n = 9) showed no difference in mortality (risk difference −0.05 per 1000 livebirths; 95% CI –5.25, 5.15). Six trials investigated anthropometry and found no difference at follow-up in weight-for-age z score (0.02; 95% CI −0.03, 0.07), height-for-age z score (0.01; 95% CI −0.04, 0.06), or head circumference (0.11 cm; 95% CI −0.03, 0.26). No differences were seen in cognitive function (with the exception of motor ability in one study), body composition, blood pressure, or respiratory outcomes. The trials were generally of high quality and differential loss to follow-up and publication bias did not appear important. Conclusions: Despite current recommendations for multiple micronutrient supplementation to replace iron and folic acid in pregnancy, the current evidence from long-term follow-up studies does not show improvements in child survival or growth.